Ons Volksonderwijs : orgaan van den Bond van Oud-Leerlingen der Stadsscholen van Gent (Gent)
"Eerste nr.: jan 1904 Beheer/Administratie : Hoogstraat 155, Gent ; Wondelgemstraat 67, Gent (feb.-maa. 1909) ; Rietstraat 95, Gent (I-1910) ; Rooigemstraat 268, Gent (dec. 1913) Drukker/Drukkerij: E. De Laere, Hoogstraat 155, GentPeriodiciteit: maandelijks"